The Predominance of Alternatively Activated Macrophages Following Challenge with Cell Wall Peptide-Polysaccharide After Prior Infection with Sporothrix schenckii - Alegranci, Pamela [UNESP]; de Abreu Ribeiro, Livia Carolina [UNESP]; Ferreira, Lucas Souza [UNESP]; Negrini, Thais de Cássia [UNESP]; Maia, Danielle Cardoso Geraldo [UNESP]; Tansini, Aline [UNESP]; Gonçalves, Amanda Costa [UNESP]; Placeres, Marisa Campos Polesi [UNESP]; Carlos, Iracilda Zeppone [UNESP] (Springer Nature, 2013)
Sporotrichosis is a subcutaneous mycosis that is caused by the dimorphic fungus Sporothrix schenckii. This disease generally occurs within the skin and subcutaneous tissues, causing lesions that can spread through adjacent lymphatic vessels and sometimes leading to systemic diseases in immunocompromised patients. Macrophages are crucial for proper immune responses against a variety of pathogens. Furthermore, macrophages can play different roles in response to different microorganisms and forms of activation, and they can be divided into classic or alternatively activated populations, as also known as M1 and M2 macrophages. M1 cells can lead to tissue injury and contribute to pathogenesis, whereas M2 cells promote angiogenesis, tissue remodeling, and repair. The aim of this study was to investigate the roles of M1 and M2 macrophages in a sporotrichosis model. Toward this end, we performed phenotyping of peritoneal exudate cells and evaluated the concomitant production of several immunomediators, including IL-12, IL-10, TGF-β, nitric oxide, and arginase-I activity, which were stimulated ex vivo with cell wall peptide-polysaccharide. Our results showed the predominance of the M2 macrophage population, indicated by peaks of arginase-I activity as well as IL-10 and TGF-β production during the 6th and 8th weeks after infection. These results were consistent with cellular phenotyping that revealed increases in CD206-positive cells over this period. This is the first report of the participation of M2 macrophages in sporotrichosis infections. © 2013 Springer Science+Business Media Dordrecht.
Keywords: CD206; Cell wall peptide-polysaccharide; Interleukin, fungus; M2 macrophages; Sporothrix schenckii; Fungi